Own system of intelligent building in comparison with an open - source solution - Kryczka, Cezary (Journal of Computer Sciences Institute, 2019)
This article is an attempt to answer the question whether and under what conditions it is beneficial to develop an own intelligent building system, when many free open source systems are available. The publication presents the characteristics of author's own home automation system - sHome, as well as the open-source system - Domoticz, in a configuration that is as close to the functionality of the author's system as possible. The work ends with a comparative analysis of the systems and conclusions from the analysis.